Evaluation of Irrigation Systems for Cost Reduction in Wide Spaced Sugarcane - Thiyagarajan, G.; Vijayakumar, M.; Selvaraj, P. K.; Duraisamy, V. K.; Yassin, M. Mohamed (International Journal of Bio-resource and Stress Management, 2023)
Field experiments were conducted at Agricultural Research Station, Tamil Nadu Agricultural University, Bhavanisagar, Tamil Nadu, India to evaluate the irrigation systems for cost reduction in wide spaced sugarcane during 2000-2004. The results revealed that, drip irrigation at 60% PE with one lateral row-1 significantly recorded higher sugarcane yield of 164.8 t ha-1 with enhanced water use efficiency of 166.1 kg ha-1 mm-1 and highest net returns of ` 83,650 ha-1. Among the surface irrigation treatments, irrigation at 1.0 IW/CPE ratio recorded the maximum yield of 140.1 t ha-1 with a WUE of 90.7 kg ha-1 mm-1.